Revision of Biserovus xiae Li, Su & Yu, 2004 (Tardigrada: Macrobiotidae) - Li, Xiaochen (Zootaxa, 2009)
Biserovus xiae Li, Su & Yu is re-described and assigned to the genus Insuetifurca. I. xiae comb. nov. (Li, Su & Yu, 2004) differs from I. arrowsmithi (Kathman & Nelson, 1989) by having a much lower pt of the pharyngeal tube and by the presence of a crescent-shaped cuticular bar behind the double claws on the first three pairs of legs; I. xiae differs from I. fujiense (Ito, 1997) by having macroplacoids equal in length or the second is the shortest instead of the macroplacoids increasing in length from the first to the third and by the presence of a crescent-shaped cuticular bar behind the double claws on the first three pairs of legs.